The use of locum doctors in the NHS: understanding and improving the quality and safety of care - Allen, Thomas; Ashcroft, Darren; Ferguson, Jane; Grigoroglou, Christos; Kontopantelis, Evan; Stringer, Gemma; Walshe, Kieran (Health and social care delivery research, 2024)
The use of locum doctors in the National Health Service is widely believed to have increased, and there have been widespread and sustained concerns among policy-makers, healthcare providers, professional associations and professional regulators about the quality/safety, cost and effective use of locum doctors. To provide evidence on the extent, quality and safety of medical locum practice and the implications of medical locum working for health service organisation and delivery in primary and secondary care in the English National Health Service, to support policy and practice. Four interlinked work packages involving surveys of National Health Service trusts and of general practices in England; semistructured interviews and focus groups across 11 healthcare organisations in England; analysis of existing routine data sets on the medical workforce in primary care and in National Health Service trusts in England from National Health Service Digital and National Health Service Improvement; and analysis of data from the Clinical Practice Research Datalink in primary care and of electronic patient record data from two National Health Service hospitals in secondary care. In primary care, about 6% of general practice medical consultations were undertaken by locums in 2010 and this had risen slightly to about 7.1% in 2021. In National Health Service trusts (mostly secondary care and mental health), about 4.4% of medical staff full-time equivalent was provided by locum doctors. But those overall national rates of locum use hide a great deal of variation. In primary care, we found the National Health Service Digital workforce returns showed the rate of locum use by Clinical Commissioning Group varied from 1% to almost 31%. Among National Health Service trusts, the reported rate of locum use varied from < 1% to almost 16%. We found that there was poor awareness of and adherence to national guidance on locum working arrangements produced by National Health Service England. Our research showed that locum working can have adverse consequences for the quality and safety of care, but that such consequences were probably more likely to result from the organisational setting and the working arrangements than they were from the locum doctors themselves and their competence, clinical practice or behaviours. Our research was hampered in some respects by the COVID pandemic which both resulted in some delays and other challenges. Our efforts to use electronic patient record data in secondary care to explore locum doctor working were stymied by the problems of data access and quality. Locum doctors are a key component of the medical workforce in the National Health Service, and provide necessary flexibility and additional capacity for healthcare organisations and services. We found that the extent of reliance on locum doctors varied considerably, but that an over-reliance on locums for service provision was undesirable. Some differences in practice and performance between locum and permanent doctors were found, but these seemed often to arise from organisational characteristics. We found that patients were more concerned with the clinical expertise and skills of the doctor they saw than whether they were a locum or not. Organisational arrangements for locum working could be improved in many respects. This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: NIHR128349) and is published in full in ; Vol. 12, No. 37. See the NIHR Funding and Awards website for further award information.